2003
DOI: 10.1007/978-3-540-39653-6_13
|View full text |Cite
|
Sign up to set email alerts
|

Tools for Studying Behavior and Technology in Natural Settings

Abstract: Abstract. Three tools for acquiring data about people, their behavior, and their use of technology in natural settings are described: (1) a context-aware experience sampling tool, (2) a ubiquitous sensing system that detects environmental changes, and (3) an image-based experience sampling system. We discuss how these tools provide researchers with a flexible toolkit for collecting data on activity in homes and workplaces, particularly when used in combination. We outline several ongoing studies to illustrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(69 citation statements)
references
References 16 publications
0
63
0
1
Order By: Relevance
“…As pointed out by Rogers (2011), new pervasive technologies should address a wider understanding on how people experience daily life, moving from laboratory to more realistic design and testing settings. Intille et al (2003) state that developing meaningful ubiquitous computing applications first requires a global understanding of how people behave in context.…”
Section: In-situ and Self-reflection Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As pointed out by Rogers (2011), new pervasive technologies should address a wider understanding on how people experience daily life, moving from laboratory to more realistic design and testing settings. Intille et al (2003) state that developing meaningful ubiquitous computing applications first requires a global understanding of how people behave in context.…”
Section: In-situ and Self-reflection Methodsmentioning
confidence: 99%
“…With ESM participants make a quick record close to the moment of interest, providing instant reports on momentary experiences instead of having to recall what they did in the past. The involvement of context-aware technologies in ESM opens the opportunity to automatize the capturing of context around participants' self-reports (Barren and Barren 2001; Consolvo et al 2006;Intille et al 2003). Furthermore, contextual information could help to adapt the timing and content of the prompts minimizing interruptions as well as tailoring the research questions according to what is been observed (Vastenburg and Romero, 2010).…”
Section: In-situ and Self-reflection Methodsmentioning
confidence: 99%
“…Context aware applications employ a broad range of sensors such as electronic tags, light sensing and physiological sensing. However, integration and the subsequent interpretation of these signals is hard, and context aware systems are likely to consider contexts differently than users do [6]. For example, when a user decides to watch a movie at home and closes the blinds to make the room darker, the system may automatically switch on the lights.…”
Section: Emerging Hci Systemsmentioning
confidence: 99%
“…They can be anywhere between responsive and pro-active. An example that lies somewhere in between responsive and pro-active is for instance the smart home described in Intille et al [6] where the system suggests users which clothes to wear given the outside temperature, or suggests measures to save energy. From a system point of view, smart homes have the task to maintain the homeostasis of the environment, and to support the users that are living in it.…”
Section: Smart Homesmentioning
confidence: 99%
“…Methodological studies have examined how audio and photographic capture impacts diary studies (see [25]), but diary methods are still prone to recollection and compliance problems when the initiative for recording all data is left to the informant. In order to study daily-life activities a sensor-based variant of experience sampling has been proposed, called the event sampling method [26]. According to Larson and Csikszentmihalyi [27] experience sampling involves prompting users to self-report at random, or at scheduled moments in the day, thereby forcing through the protocol the timing of the inquiry.…”
Section: Ambient Journalingmentioning
confidence: 99%